ISOLATION AND CHARACTERIZATION OF HYDROCARBON DEGRADING BACTERIA - SARSHAD,; DEEPESH DINESH,; NIMSI SHIRAF,; S ELVAM ARJUNAN, (International Journal of Pharma and Bio Sciences, 2015)
Petroleum refineries around the world have played major role in generating the solid wastes during the refining process and stocking of crude oil. Oily sludge leads to critical effects in the environment. The ecology of hydrocarbon degradation by microbial populations in the natural environment is analysed, highlighting the physical, chemical, and biological factors that cause the biodegradation of petroleum and individual hydrocarbons. Therefore, in the present research work ventures to isolate hydrocarbon degrading bacteria from the contaminated soil with petrol and diesel oil. In the present work study was conducted in order to decode the microorganisms from oil contaminated sites for oil degradation abilities. Ten soil samples were isolated from oil contaminated sites. One isolate MS 9 showed maximum oil degradation ability. The isolate was characterized for staining and biochemical activities based on Bergey’s Manual. The strains were preliminarily identified based on morphological observation, physiological and biochemical tests.